Response of Respiration of Soybean Leaves Grown at Ambient and Elevated Carbon Dioxide Concentrations to Day-to-day Variation in Light and Temperature under Field Conditions - BUNCE, JAMES A. (Ann Bot, 2005)
• Background and Aims Respiration is an important component of plant carbon balance, but it remains uncertain how respiration will respond to increases in atmospheric carbon dioxide concentration, and there are few measurements of respiration for crop plants grown at elevated [CO(2)] under field conditions. The hypothesis that respiration of leaves of soybeans grown at elevated [CO(2)] is increased is tested; and the effects of photosynthesis and acclimation to temperature examined. • Methods Net rates of carbon dioxide exchange were recorded every 10 min, 24 h per day for mature upper canopy leaves of soybeans grown in field plots at the current ambient [CO(2)] and at ambient plus 350 µmol mol(−1) [CO(2)] in open top chambers. Measurements were made on pairs of leaves from both [CO(2)] treatments on a total of 16 d during the middle of the growing seasons of two years. • Key Results Elevated [CO(2)] increased daytime net carbon dioxide fixation rates per unit of leaf area by an average of 48 %, but had no effect on night-time respiration expressed per unit of area, which averaged 53 mmol m(−2) d(−1) (1·4 µmol m(−2) s(−1)) for both the ambient and elevated [CO(2)] treatments. Leaf dry mass per unit of area was increased on average by 23 % by elevated [CO(2)], and respiration per unit of mass was significantly lower at elevated [CO(2)]. Respiration increased by a factor of 2·5 between 18 and 26 °C average night temperature, for both [CO(2)] treatments. • Conclusions These results do not support predictions that elevated [CO(2)] would increase respiration per unit of area by increasing photosynthesis or by increasing leaf mass per unit of area, nor the idea that acclimation of respiration to temperature would be rapid enough to make dark respiration insensitive to variation in temperature between nights.